Comparison of the educational outcome in pharmacology, among the MBBS students of CBME and pre-CBME batch: a cross-sectional study - Adaikkalavan, Umayal; Poovancheri, Hasna; Mohamedali, Seema P.; Pannikkottuthodi, Salwa; Josephine, Glory (International Journal of Basic & Clinical Pharmacology, 2026)
In 2019, the new competency based medical education (CBME) was implemented for undergraduate medical students. Competence is defined as the habitual and prudent application of communication, knowledge, technical skills, clinical reasoning, emotions, values, and reflection in everyday practice for the benefit of the individual and community being served. The objective of the newly introduced curriculum is to continue and promote medical education by making it more learner-centric, patient-centric, gender-sensitive, outcome-oriented, and environment-appropriate. Students of CBME and pre-CBME were divided in to 3 groups based on their previous academic performance. A sample size of 90 was considered, 45 students from CBME and 45 from pre-CBME batch. Students were given the questionnaire framed according to the domains of CBME curriculum. Later, assessment was done at the end and the results were compared between 2 batches. CBME curriculum students performed better than pre-CBME batch in terms of theoretical and practical knowledge, also in attitude, ethics and communication (AETCOM).